Bank Kosa Kata Untuk Tuna Rungu dan Tuna Wicara Berbasis Web - Ira Puspita Sari; Salamun; Sukri (Indonesian Society of Applied Science, 2021)
Communication is the most important key to mastering this era of globalization. There is no denying that language is the most important part of communication. When one person uses the same language or understands another person's language, they can communicate well. Sign language is a language based on artificial communication, i.e. body language and lip movements during communication. This sign language is standardized as SIBI (Indonesian Sign Language System). SIBI is one of the media in the form of books that are able to communicate with deaf people in the community. Its shape is a systematic arrangement of groups of fingers, hands and various movements, symbolizing the word Indonesian. Book media does not seem to be easily understood by users, so it takes an application that can provide moving images to facilitate sign language learning, one of which is web-based.